Climate capitalism : global warming and the transformation of the global economy - Newell, Peter (Peter John); Paterson, Matthew, 1967- (Cambridge : Cambridge University Press, 2010)
'Confronting climate change is now understood as a problem of'decarbonising' the global economy: ending our dependence on carbon-based fossil fuels. This book explores whether such a transformation is underway, how it might be accelerated, and the complex politics of this process. Given the dominance of global capitalism and free-market ideologies, decarbonisation is dependent on creating carbon markets and engaging powerful actors in the world of business and finance. Climate Capitalism assesses the huge political dilemmas this poses, and the need to challenge the entrenched power of many corporations, the culture of energy use, and global inequalities in energy consumption. Climate Capitalism is essential reading for anyone wanting to better understand the challenge we face. It will also inform a range of student courses in environmental studies, development studies, international relations, and business programmes'--
Includes bibliographical references and index.
Keywords: Emissions trading; Climatic changes -- Economic aspects; Pollution -- Economic aspects; Capitalism; Globalization